2000
DOI: 10.1002/(sici)1096-9845(200005)29:5<587::aid-eqe926>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Tuned liquid dampers for controlling earthquake response of structures

Abstract: SUMMARYNumerical simulations of a single-degree-of-freedom (SDOF) structure, rigidly supporting a tuned liquid damper (TLD) and subjected to both real and arti"cially generated earthquake ground motions, show that a properly designed TLD can signi"cantly reduce the structure's response to these motions. The TLD is a rigid, rectangular tank with shallow water in it. Its fundamental linear sloshing frequency is tuned to the structure's natural frequency. The TLD is more e!ective in reducing structural response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…With this second approach, not only the natural period of the structure is considered; the damping characteristics, inertia and restoring terms are also relevant in the dynamic analysis. Real motions of the structure are the outcome of this process and such motions can be compared with design limit states, for instance (Banerji et al 2000, Frandsen 2005, Delorme et al 2006, Attari andRofooei 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this second approach, not only the natural period of the structure is considered; the damping characteristics, inertia and restoring terms are also relevant in the dynamic analysis. Real motions of the structure are the outcome of this process and such motions can be compared with design limit states, for instance (Banerji et al 2000, Frandsen 2005, Delorme et al 2006, Attari andRofooei 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Modelling TLDs fluid responses has been conducted using a range of approaches mostly based on mechanical analogies (Tait and Deng 2008), potential flow models of the free surface fluid flow (Frandsen 2005, Attari and Rofooei 2008, Ikeda and Nakagawa 1997, Ikeda 2003 or most commonly, non-linear shallow water wave theory (Sun and Fujino 1994, Reed et al 1998, Banerji et al 2000, Tait et al 2005. None of these has tried to properly model the effects of breaking waves on increasing the dampening effects of the TLD devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the liquid tank can be used as a damper that the proper tuned liquid tank may mitigate earthquake and wind induced vibration of tall building or long span bridge. Therefore, a liquid tank is also frequently used as a TLD to reduce possible violent oscillation of the structures (Banerji et al [1][2], Sun et al [3], Reed et al [4], Fujino et al [5], and Marivani and Hamed [6]). The simple idea is the sloshing frequency of the liquid in a tank can be tuned to give a desired reaction to reduce the vibration of the structures attached with liquid tanks.…”
Section: Introductionmentioning
confidence: 99%
“…The shallow water wave theory has been used incorporating effect of braking of waves which ultimately represents a rectangular TLD as nonlinear model ). Banerji et al (2000) used the formulation suggested by [10] and [3] experimentally found inconsistency in the results which was obtained by using the formulation given by sun et al This was happened due to the lacking of actual prediction of the water surface cause by braking of the waves in the shallow water model. For the solution of this problem Samanta and Banerji (2006) [8] used a various shallow water theory and two numerical schemes, the Lax finite difference method and the random choice method, The response of SDOF system equipped with TLD subjected to severe amplitude harmonic excitation.…”
Section: Introductionmentioning
confidence: 99%